2011
DOI: 10.1016/s1473-3099(10)70312-1
|View full text |Cite
|
Sign up to set email alerts
|

Towards a conceptual framework to support one-health research for policy on emerging zoonoses

Abstract: In the past two decades there has been a growing realisation that the livestock sector was in a process of change, resulting from an expansion of intensive animal production systems and trade to meet a globalised world's increasing demand for livestock products. One unintended consequence has been the emergence and spread of transboundary animal diseases and, more specifically, the resurgence and emergence of zoonotic diseases. Concurrent with changes in the livestock sector, contact with wildlife has increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
178
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(182 citation statements)
references
References 19 publications
(23 reference statements)
0
178
0
4
Order By: Relevance
“…In order to be successful, a "One Health" approach has to be truly multidisciplinary and every component of a global/holistic approach has to be addressed proficiently in its own right. More, given the changes in the livestock sector, its contact with wildlife and the resurgence and emergence of zoonotic diseases linked to it, a new "One Health" research and policy-generation strategy has to be defined [2]. It is in this context that the World Animal Health Organization (OIE) is endorsing a "One Health" approach which will result in a deeper and sustainable political support for the coordinated prevention of high public health and animal impact diseases at the human-animal interface (http://www.oie.int/en/for-the-media/onehealth/).…”
Section: Introductionmentioning
confidence: 99%
“…In order to be successful, a "One Health" approach has to be truly multidisciplinary and every component of a global/holistic approach has to be addressed proficiently in its own right. More, given the changes in the livestock sector, its contact with wildlife and the resurgence and emergence of zoonotic diseases linked to it, a new "One Health" research and policy-generation strategy has to be defined [2]. It is in this context that the World Animal Health Organization (OIE) is endorsing a "One Health" approach which will result in a deeper and sustainable political support for the coordinated prevention of high public health and animal impact diseases at the human-animal interface (http://www.oie.int/en/for-the-media/onehealth/).…”
Section: Introductionmentioning
confidence: 99%
“…OH is an ethical, ecological approach that takes into consideration justice and respect for human and animal populations as well as the environment. (1)(2)(3) This approach considers the wider social and environmental factors that shape disease transmission, and helps us to identify three populations that are particularly vulnerable but may be overlooked in this scenario: transient foreign workers, their sexual partners and local monkey populations.…”
mentioning
confidence: 99%
“…Studies have indicated that wild animals as being the reservoir of many human infectious diseases including anthrax [44]. It is estimated that more than third of new, emerging, or re-emerging human infectious diseases since an early 21 st century have been caused by pathogens originating from animals or products of animal origin [45]. Viruses, bacteria, and parasites have had their reservoirs in a host of animals such as those found in the wild, peri-domestic, and domestic [44].…”
Section: Discussionmentioning
confidence: 99%